Integrating Religious and Economic Education for Sustainable Development Goals (SDGs): An Analysis of Entrepreneurial Models in Indonesian Pesantren - Mutmainnah; Waston; Muhammad Sholahuddin (Profetika: Jurnal Studi Islam, 2024)
Objective: This study explores the implementation of entrepreneurial models in three pesantren: Islamic Boarding School ‘A’ in Ngawi, Islamic Boarding School ‘B’ in Sukoharjo, and Islamic Boarding School ‘C’ in Surakarta. Each pesantren employs distinct approaches—namely, the in-house business model, the ‘maklon’ (outsourced production) partnership model, and the contract-based partnership model. Pesantren, as traditional Islamic educational institutions in Indonesia, have long served as centers for character-building and moral education. With the advent of global economic challenges, these institutions are tasked with bridging religious teachings and modern economic competencies, particularly through entrepreneurship education. Theoretical framework: The theoretical framework of this research integrates Islamic educational philosophy and sustainable development goals (SDGs), particularly SDG 4 (quality education) and SDG 8 (decent work and economic growth). Literature Review: A literature review reveals that entrepreneurial education contributes significantly to students' readiness for real-world challenges, fostering economic self-reliance while maintaining ethical integrity. Methods: Using a qualitative approach, this study combines case study analysis, interviews, and field observations. Results: The findings indicate that the ‘maklon’ partnership model has the most significant impact, increasing pesantren revenue and equipping Santri with practical skills in business management, marketing, and finance. Additionally, all three models emphasize ethical entrepreneurship rooted in Islamic principles, contributing to SDG 12 (responsible consumption and production). Implications: The implications of this study are profound, suggesting that pesantren can serve as hubs for sustainable economic education that aligns with religious values. By adopting entrepreneurial models, these institutions not only enhance the economic resilience of their students but also contribute to broader societal development. Novelty: The novelty of this study lies in its exploration of how pesantren-based entrepreneurship education can simultaneously advance religious and economic goals while addressing SDGs. It provides a replicable framework for integrating ethics and entrepreneurship in similar educational contexts.